'Barons' Wars, under Other Names': Feudalism, Royalism and the American Founding. Issue 2 (17th February 2017) - Nelson, Eric
SUMMARY: The Machiavellian Moment was largely responsible for establishing what remains the dominant understanding of American Revolutionary ideology. Patriots, on this account, were radical whigs; their great preoccupation was a terror of crown power and executive corruption. This essay proposes to test the whig reading of patriot political thought in a manner suggested by Professor Pocock's pioneering first book, The Ancient Constitution and the Feudal Law . The whig tradition, as he taught us, located in the remote Saxon past an 'ancient constitution' of liberty, in which elected monarchs merely executed laws approved by their free subjects in a primeval parliament. This republican idyll, whigs believed, was then tragically interrupted by the Norman Conquest of 1066, which introduced feudal tenures and monarchical tyranny. Did patriot theorists accept this narrative? The answer, I shall argue, is strikingly mixed. By the early 1770s, appeals to the 'ancient constitution' had become less common in patriot writing. And by the end of the 1770s, many patriots had absorbed a completely different understanding of the feudal past—one pioneered by Royalist historians of the seventeenth century and then adapted by Scottish historians of the eighteenth. This shift reflects a broader transformation in patriot political and constitutional theory.